Analisis Literatur Tentang Peran Mutasi Genetik dalam Terjadinya Trisomi 21 - Amelia Putri Az Zahra; Erlanda Islami Pasha; Hanayu Anindya Nareswari; Karina Sella Juwitasari; Nur Aini Fatna Fadilla; Pramesti Listanto; Rizka Fellithia; Azzahra Nabilla Atha; Liss Dyah Dewi Arini (PPNI UNIMMAN, 2026)
Down syndrome, or Trisomy 21, is the most common chromosomal disorder in humans and is primarily caused by nondisjunction events during meiosis. Although advanced maternal age has long been recognized as the major risk factor, recent scientific evidence indicates that genetic mutations, gene polymorphisms, and meiotic recombination abnormalities also play important roles in the occurrence of Trisomy 21. This literature review aims to analyze the role of genetic mutations in the pathogenesis of Trisomy 21, with emphasis on the mechanisms of nondisjunction, oocyte aging, meiotic recombination errors, and folate metabolism disorders. The method used was a narrative literature review based on seven major scientific sources discussing the genetic and molecular factors underlying Trisomy 21. The findings indicate that genetic mutations and variations affecting meiotic regulation, recombination positioning, chromosome cohesion, and DNA methylation significantly increase the risk of chromosome 21 nondisjunction. In addition, age-related decline in oocyte quality and polymorphisms in folate metabolism genes further exacerbate chromosomal instability. Understanding these mechanisms is essential for the development of genetic counseling, early detection, and more effective prevention and management strategies in the future.